[ACT Architecture, Gae Aulenti, Musée d'Orsay, Paris]
Sobre el Museo de Orsay en París por Gae Aulenti, año de proyecto 1979, finalizado en 1986.
Keywords: AULENTI, GAE; GAE AULENTI ARCHITETTI ASSOCIATI; FRANCIA; PARIS; MUSEOS; PINACOTECAS; MUSEOS DE ARTE